The Gospel among religions : Christian ministry, theology, and spirituality in a multifaith world - Brockman, David R.; Habito, Ruben L. F., 1947- (Maryknoll, N.Y. : Orbis Books, 2010)
"An indispensable collection of texts and essays focused on how the work of Christianity is affected by other religious traditions." "An urgent question in the twenty-first century is how Christians can relate to people of other religious traditions, or even non-believers, whose lives truly embody the unconditional divine love given to all at creation. How should Christians understand these differing faith claims?" "The first part of this book is comprised of original texts, beginning with the New Testament and working through the early church Fathers to contemporary theologians as they struggle to make sense of different sets of religious belief." "The essays in the second part explore ways of living together in a world of religious diversity that can broaden and deepen our understanding of other traditions and help us become more firmly rooted in our own lives as Christians." ""Imaginatively conceived and brilliantly executed, The Gospel among Religions will be an indispensable resource for all engaged in Christian ministry and theological education in the twenty-first century."---kenneth Cracknell, The Cambridge Theological Federation"--BOOK JACKET.
Includes bibliographical references (p. 235-240).
Keywords: Missions -- Theory